2022
DOI: 10.1038/s41598-022-07616-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and structural responses of the aorta to intermittent hypobaric hypoxia in a rat model

Abstract: High altitude hypoxia is a condition experienced by diverse populations worldwide. In addition, several jobs require working shifts where workers are exposed to repetitive cycles of hypobaric hypoxia and normobaric normoxia. Currently, few is known about the biomechanical cardiovascular responses of this condition. In the present study, we investigate the cycle-dependent biomechanical effects of intermittent hypobaric hypoxia (IHH) on the thoracic aorta artery, in terms of both structure and function. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In C57BL/6J mice, IH generated the already known vascular remodeling (i.e., increased IMT) [12] and elastic fiber/lamella alteration [10,18,36] effects, which were prevented or inhibited by acriflavine, pazopanib and saracatinib, thereby suggesting the involvement of VE-cadherin-related endothelial permeability. This also opens a new possibility of a mechanistic explanation for the already demonstrated IH-induced arterial stiffening [7][8][9]11].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In C57BL/6J mice, IH generated the already known vascular remodeling (i.e., increased IMT) [12] and elastic fiber/lamella alteration [10,18,36] effects, which were prevented or inhibited by acriflavine, pazopanib and saracatinib, thereby suggesting the involvement of VE-cadherin-related endothelial permeability. This also opens a new possibility of a mechanistic explanation for the already demonstrated IH-induced arterial stiffening [7][8][9]11].…”
Section: Discussionmentioning
confidence: 74%
“…The link between OSAS/IH and the structural and functional impairment of vascular endothelium has been well established in both patients and animal models. Indeed, IH induces various mechanisms, such as elevation of oxidative stress, activation of Hypoxia-Inducible Factor-1 (HIF-1) and its target genes, such as VEGF [5,6], low grade chronic inflammation and sympathetic activation that, in turn, lead to endothelial dysfunction, hypertension, vascular wall thickening and degradation of the elastic fibers [7][8][9][10][11] and atherosclerosis [3,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the first, alterations in elastic fibers predominate when subjected to physiological stresses. During the transition stage, the slope gradually increases as collagen fibers engage in the activity, indicating hyperelasticity ( Li et al, 2023 ; Wang et al, 2023 ); during the reinforcing stage, the slope reaches its maximum and the collagen fibers provide their greatest effect; during the failure stage, the sample completely shreds as the ultimate load is met ( Utrera et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The biomechanical tests performed in this study were carried out according to protocols and procedures detailed in Navarrete et al (2020) , Rivera et al (2020) , and Utrera et al (2022) . The tests are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
“… Drexler et al (2008) reported stiffening on extrapulmonary arteries (trunk, right, and left main arteries) of rats with pulmonary hypertension induced by high altitude (5,000 m). In a recent experimental study, Utrera et al (2022) described mechanical and structural alterations on descending thoracic aortas of rats as a cycle-dependent effect of the exposure to intermittent HAHH.…”
Section: Introductionmentioning
confidence: 99%